Proceedings of the 2018 SIAM International Conference on Data Mining 2018
DOI: 10.1137/1.9781611975321.36
|View full text |Cite
|
Sign up to set email alerts
|

On2Vec: Embedding-based Relation Prediction for Ontology Population

Abstract: Populating ontology graphs represents a long-standing problem for the Semantic Web community. Recent advances in translation-based graph embedding methods for populating instance-level knowledge graphs lead to promising new approaching for the ontology population problem. However, unlike instance-level graphs, the majority of relation facts in ontology graphs come with comprehensive semantic relations, which often include the properties of transitivity and symmetry, as well as hierarchical relations. These com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…For future works, we are interested in providing the personalized recommendation of articles based on the combination of article readability and the understanding ability of the user. Currently, readability of articles only evaluate the texts of articles, other modalities such as images [39] and taxonomies [8] considered to improve readers' understanding. More comprehensive document encoders such as RCNN [5] and tree LSTM [47] may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…For future works, we are interested in providing the personalized recommendation of articles based on the combination of article readability and the understanding ability of the user. Currently, readability of articles only evaluate the texts of articles, other modalities such as images [39] and taxonomies [8] considered to improve readers' understanding. More comprehensive document encoders such as RCNN [5] and tree LSTM [47] may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the two domains of relational knowledge (proteins and gene ontology) G p and G o , we denote the learning objective losses as L Gp K and L Go K . Hierarchy-aware Encoding Regularization As mentioned in Section 2.1, it is observed that some ontological knowledge can form hierarchies [8], which is typically constituted by a relation with the implicit hierarchical property, such as "subclass of", as substructures. In gene ontology, more than 50% of the triples have such relations.…”
Section: Knowledge Modelmentioning
confidence: 99%
“…They have provided an efficient and systematic solution to various knowledge-driven machine learning tasks, such as relation extraction [40], question answering [3], dialogues agents [14], knowledge alignment [6] and visual semantic labeling [10]. Existing embedding models, however, are limited to only one single view, either on the instance-view graph [2,25,42] or on the ontology-view graph [5,13].…”
Section: Introductionmentioning
confidence: 99%